SIMULATION TOOL FOR VISUAL LEARNING NETWORK TOPOLOGY - Sarmidi - (JUTEKIN (Jurnal Teknik Informatika), 2017)
Almost all aspects of human life can not be released at this time of technology, especially computer technology. It can be seen from the increasingly widespread use of computers. Advances in communications technology have an influence on the development of data processing. Data can be sent from one place to another by means of telecommunications. Computer networks are not new today. Almost in every company there is a network of computers to facilitate the flow of information within the company. Using the Delphi program, the process of understanding becomes easier and interactive. Simulation learning aids, computer-based program to address a specific problem, in this case to address the issue of the introduction of computer networks and routers operating in internetworking. In general we can know and understand the workings of routers, capable of designing a router internetworking using either hardware or software. Cost savings in understanding the use of routers and able to cope troubleshoting arising in the implementation of the use of the router. In addition, to increase knowledge and insight into the field of computer science, in particular fascination in studying computer networking, internetworking, and in-depth introduction to the router as well as a reference when facing the same problem. Keyword: Topology, Network, Learning